2015
DOI: 10.1016/j.acvd.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of non-optimal secondary medical prevention in patients with stable coronary artery disease

Abstract: Although most patients with stable CAD are receiving evidence-based medications according to guidelines, there remain subgroups at higher risk of non-optimal treatment. In particular, it might be feasible to improve prevention by focusing on patients in whom a long time has elapsed since the last coronary event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…In addition, it has been demonstrated that the cardiovascular prognosis of diabetic patients with CAD undergoing percutaneous coronary intervention is worse when the level of glycosylated hemoglobin (HbA1c) is high . However, in a context of major improvement in secondary prevention, there is a lack of recent studies evaluating these issues in patients with stable CAD who are known to be at relatively low cardiovascular risk overall . In addition, although patients with CAD with diabetes mellitus (DM) have also been shown to be at higher risk of bleeding, an event with important prognostic consequences, whether this risk may vary according to DM control (HbA1c level) has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been demonstrated that the cardiovascular prognosis of diabetic patients with CAD undergoing percutaneous coronary intervention is worse when the level of glycosylated hemoglobin (HbA1c) is high . However, in a context of major improvement in secondary prevention, there is a lack of recent studies evaluating these issues in patients with stable CAD who are known to be at relatively low cardiovascular risk overall . In addition, although patients with CAD with diabetes mellitus (DM) have also been shown to be at higher risk of bleeding, an event with important prognostic consequences, whether this risk may vary according to DM control (HbA1c level) has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Отже, основні напрямки терапії ІХС, з точки зору доказової медицини, повинні бути спрямовані саме на ці фактори ризику. Недосконалість кардіологічної допомоги населенню і нераціональне використання заснованих на фактичних даних препаратів у пацієнтів з ІХС пов'язані з підвищеним ризиком несприятливого результату терапії [6] і високим рівнем серцево-судинної смертності [1,4,7,9,11,12].…”
unclassified